2018
DOI: 10.1038/s41598-018-23958-3
|View full text |Cite
|
Sign up to set email alerts
|

Aligned laminin core-polydioxanone/collagen shell fiber matrices effective for neuritogenesis

Abstract: Neural tissue regeneration is a significant challenge, because severe nerve injury is quite difficult to regenerate spontaneously. Although, many studies have been devoted to promote nerve regeneration, there are still many technical challenges to achieve satisfactory results. In this study, we designed biomimetic matrices composed of aligned laminin core-polydioxanone/collagen shell (Lam-PDO/Col) fibers, which can provide both topographical and biochemical cues for promoting neuritogenesis. The aligned Lam-PD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
22
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 84 publications
2
22
0
2
Order By: Relevance
“…In vitro cytotoxic study revealed that all groups in the study were not cytotoxic, and the cells grew as layers on the mat for 5 days as shown by SEM images. Notably, the reported tri-layered mats with highly sustained drug release profile are easy and straight forward to fabricate when compared to other methods such as coaxial / triaxial / microfluidic methods 3,17,[19][20][21][55][56][57][58] , hence can serve as a potential drug delivery vehicle in clinical applications. In summary, 12% PCLSW-2 with controlled initial burst and sustained release for 62 days, compared to all other groups in evaluation, seems to be best suited for delivery of IBU.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In vitro cytotoxic study revealed that all groups in the study were not cytotoxic, and the cells grew as layers on the mat for 5 days as shown by SEM images. Notably, the reported tri-layered mats with highly sustained drug release profile are easy and straight forward to fabricate when compared to other methods such as coaxial / triaxial / microfluidic methods 3,17,[19][20][21][55][56][57][58] , hence can serve as a potential drug delivery vehicle in clinical applications. In summary, 12% PCLSW-2 with controlled initial burst and sustained release for 62 days, compared to all other groups in evaluation, seems to be best suited for delivery of IBU.…”
Section: Discussionmentioning
confidence: 99%
“…Various studies have reported the merits of coaxial/tri-axial fabrication of nanofibrous for sustained release of drugs 3,[19][20][21] . Although such methods yield efficient nanofiberous systems for controlled drug release, the complexity of fabrication process is a drawback.…”
mentioning
confidence: 99%
“…They showed that such biomaterials promoted neural differentiation of mouse embryonic stem cells (ES-D3 cell line). Song et al [258] produced electrospun polydioxanone/collagen (PDO/Col) and laminin/polydioxanone/collagen (Lam-PDO/Col) core-shell matrices. They demonstrated that Lam-PDO/Col biomaterial possessed interconnected porous structure and moderate mechanical properties (E close to 2.5 MPa).…”
Section: Nerve Tementioning
confidence: 99%
“…Even when using an insoluble carrier to achieve sustained release profiles, because of the presence of a substantial quantity of drug at or near the surface of the composite, an initial burst release and eventual tailoring-off are inevitable. Very significant efforts have been made to overcome these issues, including through the fabrication of a range of electrospun nanofibers [63,64]. In the core-shell nanohybrids prepared by modified triaxial electrospinning (F2, F3, F4), a blank CA coating was applied to yield a product with a heterogeneous distribution of drug (Fig.…”
Section: Process-structure-performance Relationshipsmentioning
confidence: 99%